Malay happiness at workplace index: psychometric properties study - AHD, Latfi; S, Mohamed Saini; A, Baharudin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present study aimed to validate the Malay Happiness at Workplace (M-HAW) index questionnaire. A cross-sectional survey study with a convenience sampling method was carried out at Universiti Kebangsaan Malaysia Medical Centre (UKMMC), Malaysia. The forward-backward approach was used to translate the original 11 items of the M-HAW questionnaires, which were then distributed to respondents. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were utilised to assess the questionnaires’ validity and reliability. A total of 501 healthy individuals were included in the study, with 72% female respondents and a mean age of 37.63 + 7.60. The questionnaire was generally well-received by participants, and reliability standards were met (Cronbach’s α = 0.95). The EFA shows two distinct factors, namely individual and environmental factors. The CFA shows that the model was fit (RMSEA= 0.076, CFI= 0.978, x2/df= 3.31). The M-HAW demonstrated its validity as a good tool for determining happiness in the workplace. The M-HAW questionnaire can be used as a screening tool to measure happiness, and should be able to help an organisation provide suitable interventions to improve employee happiness.